2018
DOI: 10.1021/acs.cgd.7b01771
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Attachment: A Path to Columnar Morphology in Chemical Bath Deposited PbSe Thin Films

Abstract: We have studied columnar PbSe thin films obtained using chemical bath deposition. The columnar microstructure resulted from an oriented attachment growth mechanism, in which nuclei precipitating from solution attached along preferred crystallographic facets to form highly oriented, size-quantized columnar grains. This is shown to be an intermediate growth mechanism between the ion-by-ion and cluster growth mechanisms. A structural zone model depicting the active growth mechanisms is presented for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…99 Templeton et al reported a unique morphology controlled by substrate temperature during their CBD deposition process. 100 By varying the substrate temperature between 15-40 1C, they were able to obtain distinct PL signals ranging from 1.9-4.4 mm in wavelength, respectively. 100 The deposition rate was slow; however, the columnar morphology could be beneficial for maximizing absorption by scattering light.…”
Section: Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…99 Templeton et al reported a unique morphology controlled by substrate temperature during their CBD deposition process. 100 By varying the substrate temperature between 15-40 1C, they were able to obtain distinct PL signals ranging from 1.9-4.4 mm in wavelength, respectively. 100 The deposition rate was slow; however, the columnar morphology could be beneficial for maximizing absorption by scattering light.…”
Section: Sourcementioning
confidence: 99%
“…100 By varying the substrate temperature between 15-40 1C, they were able to obtain distinct PL signals ranging from 1.9-4.4 mm in wavelength, respectively. 100 The deposition rate was slow; however, the columnar morphology could be beneficial for maximizing absorption by scattering light. There was no mention of sensitization.…”
Section: Sourcementioning
confidence: 99%
“…Furthermore, CD facilitates efficient control over thin film properties. 14,15,17 For example, the thin films of PbS, an important semiconductor with optoelectronic properties applicable for infrared detection and solar cells, 18−21 can be grown on GaAs with unprecedented quality 22 and transformed from nanocrystalline to monocrystalline by controlling growth parameters in CD. 23 However, the main drawback of CD is the depletion of reactant concentrations, giving rise to spatial non-uniformities and limiting the maximum achievable film thickness.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One of the materials known for their chemical inertness is Teflon, a common chemically resistant polymer used in numerous applications. Although Teflon is considered inert, it has been showed to release trace amounts of impurities under specific conditions. , In this case study, we identify Teflon parts as a source of impurities and study their effect on thorium-alloyed PbS thin films prepared using chemical solution deposition (CD), which have been extensively studied in our group. We examined how contaminants, originating from the Teflon sample holder, degrade the short wave infrared (SWIR) response of our films. These findings add to the cumulative knowledge on the role of impurities in materials preparation and are relevant for practically all chemists involved in chemical synthesis.…”
Section: Introductionmentioning
confidence: 99%